Development of Scientific Learning System Based on Character Education (Honest, Discipline, Self-Confidence) in MTs-Al Maidah Deli Serdang Regency - Hutasuhut, Julianto (International Journal for Educational and Vocational Studies, 2019)
A development must start from the human factor, namely education, organization and discipline. Therefore, aspects and problems of education are the most important elements that must be addressed immediately so that national development goals can be better achieved. One area that needs attention in the field of education development is the village of Kotasan located in Galang District, Deli Serdang Regency, North Sumatra. The majority of the population is educated middle to lower causing most of the population is still living from the agricultural sector. Seeing the existing phenomena and if this condition is allowed to continue then it is feared that the welfare of the community will lead to worse conditions. So with this dedication the team will try to find solutions to educational problems that are more beneficial for the Kotasan village community. This service aims to: 1). Designing teacher working groups in applying scientific learning, 2). Designing the learning process using a scientific learning model based on Islamic character education, 3). Designing learning material that will be applied by teachers in scientific learning based on Islamic character education. The method used in this service is coaching techniques. Expected outputs from this dedication are ISSN journals, mass media and activity videos. In the process of character evaluation in every aspect, in general get a value, namely (1) Honesty as much as 90%, (2) Discipline as much as 80%, and (3) confidence as much as 85%. Then in the process of character evaluation in each aspect of points in particular there are 10 points get a value, namely: (1) honest in action 78%, (2) honest in words 80%, (3) admit mistakes 70%, (4) wake up on time morning 83%, (5) prayer 5 time 90%, (6) diligently praying 84%, (7) attending ceremonies and on time 63%, (8) gathering assignments on time 72%, (9) able to be a leader for example Imam prays 74%, and (10) 80% practice test.